A comparative analysis of the accumulation of lead acetate in blood plasma, urine and homogenates of hard dental tissues in rats - Kutsevlyak, Valentina; Bobrovska, Natalia; Belikov, Konstantin; Sheina, Tatyana (ScienceRise: Medical Science, 2017)
Aim. A comparative analysis of lead acetate concentration in blood plasma, urine and homogenates of hard dental tissues in rats for determination of the informative value of indicators to estimate condition of lead acetate accumulation and metabolism depending on its accumulation degree. Methods. The studies were carried out using 36 white mongrel male rats weighing 200–250 g. The animals were divided into two groups: the first (12 rats) – the control group, receiving ordinary water, the second group (24 rats) – the animals received lead acetate in a dose of 10 mg / kg of the the animal weight of in the form of a one-percent intragastric solution with drinking water daily during one, two and three months. Results. In result of research devoted to determination of lead acetate in blood plasma, urine and homogenates of hard dental tissues in rats, its increase depending on the poisoning period duration was found, and the highest indices were marked after 3 months period. Conclusion. A comparative analysis of the accumulation of lead acetate in blood plasma, urine and homogenates of hard dental tissues in rats using atomic absorption spectrometry was carried out. In result of the study we can conclude about the degree of lead acetate accumulation in homogenates of hard dental tissues and about the presence of subchronic lead intoxication (blood plasma, urine)